سیرت طیبہ کی روشنی میں مزاہب عالم کے مقدسات کی تکریم اور رعایت : شخصیات ، مقامات، کتب، تہوار - ڈاکٹر محم عرفان، حافظ معظم شاہ, (Seerat Studies, 2024)
There is no doubt, that, this world is converted into a global village today. So, the problems of different nations are not individual anymore, rather, they have become a collective thing. An Issue that occurs anywhere in the world would disturb the whole world somehow. The sacredness of the religion is a highlight of these issues that can disturb peace globally. Every religion has some sacred things, which are always regarded as respectable by all. If anybody attempts to disgrace the sacredness of any other religion, his act is considered as enmity and outrage against this system.